Psychological distress and its association with functional disability index among acne patients attending dermatology clinics in the Kuantan tertiary hospitals - Samsudin, Suhaiza; Zulkifli, Zuliyasmin; Hassan, Noor Artika; Ismail, Rasimah; Ramalingam, Rajalingam (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2024)
Introduction: Acne is the most common skin disease among adolescents and has significant psychological distress. Our objective is to assess acne severity, functional disability, and its psychological distress among acne patients. Methods: A cross-sectional study was conducted from November 2021 to May 2022 among 163 acne patients attending Dermatology Clinics in the district of Kuantan, Pahang. The severity of acne was graded using the Comprehensive Acne Severity Scale (CASS). The functional disability index was measured using a Cardiff Acne Disability Index (CADI), while Depression, Anxiety and Stress Scale (DASS-21) questionnaires were used as a screening tool to detect the psychological distress of acne. Data were analysed using a Chi-square test, Fisher’s exact test and multiple logistic regression. Results: The mean age was 23 years, 60.1% were female, 94.5% were Malay, and 68.1% were unemployed. The severity of acne was more prominent in the mild (30.7%) and moderate (28.2%) categories. A total of 20.2%, 11.7%, and 4.9% of the respondents had anxiety, depression, and stress symptoms, respectively. Regarding the respondents’ functional disability, 40.5% had mild impairment, 38.0% had moderate impairment, and 13.5% had severe impairment. Acne severity was found to be significantly associated with the functional disability index (P<0.05). The functional disability index was also found to be significantly associated with depression (p=0.019) and anxiety symptoms (p=0.042). Conclusion: Clinical management of acne patients should include not only pharmacological treatment but also consideration of the disease’s functional disability status and psychological distress. Malaysian Journal of Medicine and Health Sciences (2024) 20(1):126-133. doi:10.47836/mjmhs.20.1.17